Writers as Public Intellectuals Literature, Celebrity, Democracy - Heynders, Odile; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
This book demonstrates how authors performing the role of a public intellectual discuss ideas and opinions regarding society while using literary strategies and devices in and beyond the text. Their assumed persona thereby reads the world as a book - interpreting it and offering alternative scenarios for understanding it.
Keywords: Literature; Culture -- Study and teaching; Literature -- Philosophy; Literature -- History and criticism; Literature, Modern -- 20th century; European literature; Democracy; Literature; European Literature; Twentieth-Century Literature; Literary Theory; Cultural Theory; Democracy; Literary History; Electronic books